The Kano Model Use to Evaluate the Perception of Intelligent and Active Packaging of Slovak Customers (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2018)
Intelligent innovation represents any autonomic change with positive impact to the customer. They increase the comfort of the customer and concurrently they represent more effective, more economical, healthier and safer solution. This term is not so usual in Slovakia, however intelligent innovation are present on the market. For that in the article intelligent innovation assessment, we focused on intelligent and active packaging, the occurrence of which we have mostly noticed on the Slovak market. The paper deals with the evaluation of the perception of packaging innovations by using the Kano model. According to research results, intelligent and active packaging influence customers and therefore constitutes a tool of competitiveness in Slovakia. However, considering the specification of their requirements, the degree of impact is very variable and specific to customers of different gender and age.